Episodes of environmental stability versus instability in Late Cenozoic lake records of Eastern Africa. Issue 87 (October 2015) - Trauth, Martin H.; Bergner, Andreas G.N.; Foerster, Verena; Junginger, Annett; Maslin, Mark A.; Schaebitz, Frank
Abstract: Episodes of environmental stability and instability may be equally important for African hominin speciation, dispersal, and cultural innovation. Three examples of a change from stable to unstable environmental conditions are presented on three different time scales: (1) the Mid Holocene (MH) wet–dry transition in the Chew Bahir basin (Southern Ethiopian Rift; between 11 ka and 4 ka), (2) the MIS 5–4 transition in the Naivasha basin (Central Kenya Rift; between 160 ka and 50 ka), and (3) the Early Mid Pleistocene Transition (EMPT) in the Olorgesailie basin (Southern Kenya Rift; between 1.25 Ma and 0.4 Ma). A probabilistic age modeling technique is used to determine the timing of these transitions, taking into account possible abrupt changes in the sedimentation rate including episodes of no deposition (hiatuses). Interestingly, the stable-unstable conditions identified in the three records are always associated with an orbitally-induced decrease of insolation: the descending portion of the 800 kyr cycle during the EMPT, declining eccentricity after the 115 ka maximum at the MIS 5–4 transition, and after ∼10 ka. This observation contributes to an evidence-based discussion of the possible mechanisms causing the switching between environmental stability and instability in Eastern Africa at three different orbital time scales (10, 000 to 1, 000, 000 years) during the Cenozoic. This in turn may lead to great insights into the environmental changes occurring at the same time as hominin speciation, brain expansion, dispersal out of Africa, and cultural innovations and may provide key evidence to build new hypotheses regarding the causes of early human evolution.